Modified Adenosines Sensitize Glioblastoma Cells to Temozolomide by Affecting DNA Methyltransferases - Proto, Maria Chiara; Fiore, Donatella; Piscopo, Chiara; Laezza, Chiara; Bifulco, Maurizio; Gazzerro, Patrizia (Frontiers in Pharmacology, 2022)
Glioblastoma (GBM) is the most common and lethal primary malignant brain tumor and, due to its unique features, its management is certainly one of the most challenging among all cancers. N6-isopentenyladenosine (IPA) and its analogue N6-benzyladenosine (N6-BA) are modified nucleosides endowed with potent antitumor activity on different types of human cancers, including GBM. Corroborating our previous finding, we demonstrated that IPA and N6-BA affect GBM cell lines proliferation by modulating the expression of the F-box WD repeat domain-containing-7 (FBXW7), a tumor suppressor with crucial role in the turnover of many proteins, such as SREBPs and Mcl1, involved in malignant progression and chemoresistance. Luciferase assay revealed that IPA-mediated upregulation of FBXW7, translates in transcriptional inactivation of its oncogenic substrates (Myc, NFkB or HIF-1α). Moreover, downregulating MGMT expression, IPA strongly enhances the killing effect of Temozolomide (TMZ), producing a favourable sensitizing effect starting from a concentration range much lower than TMZ EC50. Through DNA-methyltransferases (DNMTs) activity assay, analysis of the global DNA methylation and the histone modification profiles, we demonstrated that the modified adenosines behave similarly to 5-AZA-dC, known DNMTs inhibitor. Overall, our results provide for the first-time new perspectives suggesting the modified adenosines as epigenetic tools able to improve chemo- and radio-therapy efficacy in glioblastoma and potentially other cancers.